Co-segregation of Mg and Zn atoms at the planar η1-precipitate/Al matrix interface in an aged Al–Zn–Mg alloy. (August 2020) - Cheng, Bingqing; Zhao, Xiaojun; Zhang, Yong; Chen, Houwen; Polmear, Ian; Nie, Jian-Feng
Abstract: Using aberration-corrected scanning transmission electron microscopy, the interface between η 1 -precipitates and Al matrix in the aged Al–2.1Zn–1.7Mg (at.%) alloy has been investigated. Atomic-resolution X-ray dispersive spectroscopy mapping reveals the occurrence of co-segregation of Mg and Zn atoms in the 002 α habit plane of the η 1 (MgZn2 ) precipitates. Site-specific Mg atoms segregate outside the concave of an outermost zig-zag Zn-rich layer of the η 1 habit plane. Zn segregation surround the segregated Mg atomic columns was also observed. Hybrid molecular dynamics (MD) and Monte Carlo (MC) atomistic simulations with the accuracy of density functional theory indicate the site-specific segregation is energetically favourable. Graphical abstract: Image, graphical abstract